Notes Towards Gritty Fantasy Medievalism, Temporality, and Worldbuilding - Anna Bark Persson (Fafnir, 2022)
This article discusses gritty fantasy, a fantasy subgenre, which was established in the early 2000s and has since gained a lot of traction. In previous research, gritty fantasy has often been understood as a deconstructive form of fantasy that draws on the barbaric Middle Ages and subverts fantasy tropes as a reaction against earlier forms of popular fantasy. I examine, rather, the genre’s relation to the medieval and its depictions of power. Drawing on queer temporality and theories on fantasy literature and worldbuilding (Mendlsohn; Roine), I approach gritty fantasy first and foremost as a form of fantasy literature, placing it within the context of speculative fiction and asking what it does as a fantastic literature.